The Analysis of Taxpayer Compliance Related to Tax Amnesty Policy at Tax Office Tabanan - N L K M Windari; W H Utthavi; N W D Ayuni (Jurusan Akuntansi Politeknik Negeri Bali, 2018)
This study aimed to know the successful implementation of tax amnesty policy to improve taxpayer compliance at Tax Office Tabanan. The analysis technique used in this study is comparative method by using statistical test. The statistical test performed are Normality Test, Homogeneity Test, and Independent Sample T-Test that used to test the level of taxpayer compliance that measured using four indicators, namely: (1) Amount of Tax Receipts; (2) Number of Administrative Sanctions Issued; (3) Number of Taxpayers Who Late In Delivering Periodic Tax Return (Income Tax Article 21); and (4) Amount of Notice of Tax Collection Issued. Data of these four indicators measured in the period before tax amnesty policy was enacted (1 October 2015 until 30 June 2016) and the period after tax amnesty policy was enacted (1 April 2017 until 31 December 2017). The results of this study showed that there are no significant difference between taxpayer compliance after the enactment of tax amnesty policy and before the enactment of tax amnesty policy. This condition occur because the effect of tax amnesty can be seen in long term, low participation of taxpayers on tax amnesty program, and low awareness of taxpayers on their tax obligations.